Action to address the household economic burden of non-communicable diseases. Issue 10134 (19th May 2018) - Jan, Stephen; Laba, Tracey-Lea; Essue, Beverley M; Gheorghe, Adrian; Muhunthan, Janani; Engelgau, Michael; Mahal, Ajay; Griffiths, Ulla; McIntyre, Diane; Meng, Qingyue; Nugent, Rachel; Atun, Rifat
Summary: The economic burden on households of non-communicable diseases (NCDs), including cardiovascular diseases, cancer, respiratory diseases, and diabetes, poses major challenges to global poverty alleviation efforts. For patients with NCDs, being uninsured is associated with 2–7-fold higher odds of catastrophic levels of out-of-pocket costs; however, the protection offered by health insurance is often incomplete. To enable coverage of the predictable and long-term costs of treatment, national programmes to extend financial protection should be based on schemes that entail compulsory enrolment or be financed through taxation. Priority should be given to eliminating financial barriers to the uptake of and adherence to interventions that are cost-effective and are designed to help the poor. In concert with programmes to strengthen national health systems and governance arrangements, comprehensive financial protection against the growing burden of NCDs is crucial in meeting the UN's Sustainable Development Goals.